The Relationship Between Modern Leadership Styles and the Development of Middle Management Leaderships - Hanania, Hanna; Al-Jamal, Sameer; Jaradat, Nasser (Ahliya Journal of Business Technology and MEAN Economies, 2024)
The study aimed to explore the relationship between modern leadership styles and the preparation of middle management leaders in municipalities within Bethlehem Governorate. A questionnaire was employed as the primary data collection tool, adopting a descriptive-analytical methodology. A stratified random sample comprising 136 employees from Bethlehem municipalities was utilized. The study’s findings revealed that the practice of leadership styles in municipalities was of a moderate degree, with the most frequently practiced modern leadership styles being digital leadership, situational leadership, agile leadership, participatory leadership, innovative leadership, transformational leadership, and flexible leadership. The results also indicated that Bethlehem municipalities prepare middle management leaders at a moderate level. Furthermore, a positive correlation was identified between all modern leadership styles (transformational, situational, participatory, flexible, digital, agile, and innovative) and the preparation of middle management leaders. The study concluded with several recommendations, most notably urging leadership in Bethlehem municipalities to focus more on modern leadership styles due to their vital role in preparing emerging and alternative leaders. It also recommended developing leadership skills through targeted training programs and encouraging leaders to provide employees with opportunities to express their opinions and participate in policy-making. The originality of this study lies in its exploration of the relationship between modern leadership styles and the preparation of middle management leaders in the context of municipalities in Bethlehem Governorate, a subject that has been underrepresented in prior research.